Identification Of Soil Resistivity Distribution In Ekoriparian Leuwi Padjadjaran Area Using 2D Electrical Resistivity Method - Prameswary, Cevilla Amalia; Donita, Fataya Tasya; Rohman, Muhammad Alkuansinta; Saeful Ihsan, Muhammad Raihan; Agustine, Eleonora (Universitas Islam Negeri Ar-Raniry, 2024)
Research focused on the identification of soil resistivity distribution at the Ekoriparian Leuwi Padjadjaran area, University of Padjadjaran, Jatinangor, has been conducted using geoelectric resistivity method 2D with dipole - dipole configuration. Three survey lines were measured with the first and second lines being 2 meters long and the third line measuring 6 meters. Electrode spacing was set at 0.2 meters, with 10 electrodes on the first and second lines, and 30 electrodes on the third line. Data processing is done using the Res2Dinv software. The research results indicated that resistivity values in the range of 4.00 Ωm to 20.0 Ωm were interpreted as clay rocks, values from 20 Ωm to 200 Ωm were interpreted as silt rocks, and resistivity values in the range of 256 Ωm to 1024 Ωm were interpreted as sandy clay rocks. Based on the geology of the study area, the soil is a fine-grained soil, namely silt and sandy loam.